As one : individual action, collective power - Baghai, Mehrdad; Quigley, James (Portfolio Penguin, 2011)
Offers a look at the power of collaboration, defining eight archetypes of leaders and followers and then explaining how readers can take different cases of successful collective behavior and apply them to their own organizations.